2022
DOI: 10.5582/irdr.2022.01079
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge level of medical students and physicians about rare diseases in Lima, Peru

Abstract: rare diseases, orphan drugs, medical students, physicians, knowledge Rare diseases (RDs) affect up to 8% of the world's population, and unfortunately, health professionals have a low level of knowledge regarding the impacts of RDs on the social, psychological, and economic spheres of the patients and their families; hence, RD management is inadequate, consistently empirical, and precarious. The objective of this study was to determine the knowledge level of the medical students from a non-state university and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…This study con rmed previous ndings from other countries that medical students generally lack knowledge and awareness of RD [19,20,[23][24][25]. While there was some disagreement between the two groups of respondents in our research, they largely found common ground on the most important issues and expressed support for similar measures to improve undergraduate training in RD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study con rmed previous ndings from other countries that medical students generally lack knowledge and awareness of RD [19,20,[23][24][25]. While there was some disagreement between the two groups of respondents in our research, they largely found common ground on the most important issues and expressed support for similar measures to improve undergraduate training in RD.…”
Section: Discussionsupporting
confidence: 90%
“…In all the studies conducted so far, medical students acknowledged the need for more concentrated training in RD by mentioning elective courses in RD and inviting lectures by RD experts as potential options to boost medical undergraduate education on RD. Participation in RD research projects and scienti c events is also welcome by the respondents to those surveys [19,20,[23][24][25][26][33][34][35][36]. In our study, we witnessed comparable gaps in knowledge in both students trained in Bulgarian and in English.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Si bien, los padres de familia suelen ser los primeros en notar los síntomas de sus hijos con probable DMD, motivo por el cual acuden a un profesional de la salud. Es importante fortalecer la educación médica en estas enfermedades genéticas (24), desde su sintomatología hasta las posibilidades terapeúticas disponibles, con el fin de que al momento de solicitar los estudios auxiliares (bioquímicos, electromiográficos, moleculares, etc) sean los más concordantes con la clínica del paciente, para que el diagnóstico de la enfermedad sea más temprana; el cual además repercutirá en un asesoramiento genético exacto, permitiendo la búsqueda de pacientes precozmente, así como la detección de portadoras (25). La prueba de creatina fosfoquinasa (CPK) podría enfatizarse en la atención primaria como una prueba de rutina en los exámenes de los niños con sospecha de esta enfermedad (26,27).…”
Section: Discussionunclassified
“…This disparity in research can also indicate that many Latin American patients do not receive adequate diagnosis, counseling, and treatment, which also limits our capacity to better understand disease mechanisms and modifiers. Likely underlying reasons include limited funding for genetic testing and research, [118][119][120] lack of knowledge of health professionals, [121][122][123] and the perception of a lower clinical utility of genetic testing by clinicians. 124 Understanding the frequency and distribution of monogenic parkinsonism is crucial for the development of clinical trials and targeted medicine.…”
mentioning
confidence: 99%